Using blackboard collaborate, a digital web conference tool, to support nursing students placement learning: A pilot study exploring its impact. (July 2019) - Hart, Tania; Bird, David; Farmer, Robert
Abstract: Ensuring student nurses, when in clinical placement areas, receive good quality Higher Education Institution (HEI) lecturer support is challenging. This is because conventional HEI placement support, is resource intensive and arguably infeasible with growing student numbers. Evidence suggests, however, that online collaborative learning solutions (e.g., virtual classrooms, web conferencing tools) have the potential to ameliorate resource pressures. To test this idea, an online learning solution called Blackboard Collaborate was piloted. It virtually connected, students and their preceptors to a university lecturer. Its usefulness was explored by obtaining qualitative, focus group data, from the students and preceptor participants. The findings were thematically analysed. Collaborate ensured all three parties were connected. It was a time efficient, easy to use technology. Despite technical glitches, i.e. occasional time delay and audio echo, participants concluded Collaborate was an efficient medium when placement needs were routine. Face-to-face was preferable when more intensive support was required. In today's busy times, HEI's must explore time effective methods of placement collaboration. Online collaborative tools are one solution. Students will, however, need to develop their digital literacy in using this technology. The benefit being when qualified they are more likely to embrace this form of technology to promote their efficiency.